(Just) first time lucky? The impact of single versus multiple bank lending relationships on firms and banks' behavior - Giorgia Barboni; Tania Treibich (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2012)
The widespread evidence of multiple bank lending relationships in credit markets suggests that firms are interested in setting up a diversity of banking links. However, it is hard to know from the empirical data whether a firm's observed number of lenders is symptomatic of financial constraints or rather a well-designed strategy. By setting up a model and testing it in a controlled laboratory experiment we are able to uncover the conditions favoring multiple versus single lending strategies of borrowers, as well as the probability to get funding from lenders. We find that borrowers adjust the way they signal their trustworthiness according to the experimental design: they do so by choosing a single lending strategy when the asymmetry of informations is high. Multiple lending is therefore strategically chosen by dishonest borrowers. Instead, when relationship building is possible, the single lending choice reinforces the positive effect of repeatedly interacting with the same lender. In this case, multiple lending is related to borrowers' financial constraints. Finally, when information upon borrowers' behavior is made available, lenders are more likely to punish free-riding behaviors than simple default due to project failure.
Keywords: C72; C73; C92; G21; 330; Repeated Games; Information Asymmetries; Multiple Lending; Relationship Lending